Pelaksanaan Identifikasi dan Asesmen bagi Anak Berkesulitan Belajar di SD Negeri 63 Surabayo Lubuk Basung Kab. Agam - Yuliana Putri; Asep Ahmad Sopandi (Jurnal Penelitian Pendidikan Khusus, 2019)
ABSTRACTThis study based on to find out and describe the identification and assessment design, implementation of identification and assessment, evaluation of identification and assessment for children with learning disabilities in 63 Surabayo Elementary School, Lubuk Basung, Agam. This study used a descriptive research method with a qualitative approach conducted at 63 Surabayo Elementary School in Lubuk Basung, Agam. The research subjects are Special Education Teachers (SET). The technique of collecting data uses are observation, interviews and documentation. The validity of the data is tested using triangulation techniques. The results of this study indicate that the process of identifying learning difficulties is carried out by classroom teachers, then the problematic identified students are reported to special education teachers, after that special education teachers at the school with the source center special education teachers work together to carry out the assessment. After the assessment process has been completed, the center's special education teacher will prepare an individual learning program which will be given to special education teachers and classroom teachers of each difficulty learning students to carry out. ABSTRAKPenelitian ini dilatarbelakangi untuk mengetahui dan mendeskripsikan tentang rancangan identifikasi dan asesmen, pelaksanaan identifikasi dan asesmen serta evaluasi identifikasi dan asesmen  bagi anak berkesulitan belajar di SD Negeri 63 Surabayo Lubuk Basung Kabupaten Agam. Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan kualitatif yang dilakukan di SD Negeri 63 Surabayo Lubuk Basung Kabupaten Agam. Subjek peneliitian yaitu Guru Pembimbing Khusus (GPK). Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Keabsahan data diuji menggunakan triangulasi teknik. Hasil dari penelitian ini menunjukkan bahwa proses identifikasi anak berkesulitan belajar dilakukan oleh guru kelas, kemudian siswa yang teridentifikasi bermasalah dilaporkan kepada guru pendidikan khusus, setelah itu guru pendidikan khusus di sekolah tersebut bersama guru pendidikan khusus pusat sumber bekerja sama melaksanakan asesmen. Setelah proses asesmen selesai dilaksanakan guru pendidikan khusus pusat sumber menyusun program pembelajaran individual yang kemudian diberikan kepada guru pendidikan khusus dan guru kelas masing–masing anak berkesulitan belajar untuk dilaksanakan.